A survey of the people displaced through the Koyna Dam, July 1965 to January 1967 - Karve, Irawati Karmarkar, 1905-1970 (Deccan College building centenary and silver jubilee series, 1969)
Report of a survey made to investigate the human problems caused by the construction of a dam in Maharashtra.